2019
DOI: 10.1016/j.aquatox.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicological effects induced by up-regulation of miR-137 following triclosan exposure to zebrafish (Danio rerio)

Abstract: Triclosan (TCS) is a prevalent anthropogenic contaminant in aquatic environments and its chronic exposure can lead to a series of neurotoxic effects in zebrafish. Both qRT-PCR and WISH identified that TCS exposure resulted in significant up-regulation of miR-137, but downregulation of its regulatory genes (bcl11aa, MAPK6 and Runx1). These target genes are mainly associated with neurodevelopment and the MAPK signaling pathway, and showed especially high expression in the brain. After overexpression or knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These studies also reported dose dependent increase in mortality and bioaccumulation of TCS in the organisms. Because of lipophilicity, TCS has the potential for bioaccumulation in the food web 9 and is considered to be hazardous for the environment and life even at low concentration. Destructive impacts of TCS on aquatic organisms include, endocrine disruption 10 , neurotoxicity 11 , mitochondrial dysfunction 12 , oxidative stress due to increased production of various reactive oxygen species (ROS), alteration of the activity of antioxidative, detoxification and metabolic enzymes and impairment of immune system 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies also reported dose dependent increase in mortality and bioaccumulation of TCS in the organisms. Because of lipophilicity, TCS has the potential for bioaccumulation in the food web 9 and is considered to be hazardous for the environment and life even at low concentration. Destructive impacts of TCS on aquatic organisms include, endocrine disruption 10 , neurotoxicity 11 , mitochondrial dysfunction 12 , oxidative stress due to increased production of various reactive oxygen species (ROS), alteration of the activity of antioxidative, detoxification and metabolic enzymes and impairment of immune system 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Triclosan caused ventriculomegaly, a decrease in the neuronal cell count, formation of the glial scars accompanied by abnormal glial cell proliferation in adult zebrafish. [ 62 ] Hematoxylin and eosin staining of the adult zebrafish spinal cord displayed a decreased number of glial cells and altered fiber structures in triclosan‐treated groups. These changes induced hearing and vision abnormalities in the zebrafish.…”
Section: Triclosan Induced Neurotoxicitymentioning
confidence: 99%
“…Behavioral findings also established that both, induced overexpression of miR‐137 and triclosan exposure (which caused overexpression of miR‐137) contributed to hearing or vision impairment in zebrafish thus providing a unique mechanism for triclosan induced neurotoxicity. [ 62 ]…”
Section: Triclosan Induced Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analysis showed that several aberrant miRs were greatly dysregulated in injured spinal cords at 4 h post IR (Figure 2A). Among these miRs, miR-137-3p has been indicated to be closely associated with neurodevelopment and CNS disease and to be highly expressed in the brain [30,33].…”
Section: Ir-induced Aberrant Spinal Mir-137-3p Expression and Negativmentioning
confidence: 99%